Deviation Cost Allocation of DISCOM Using Shapley Value. Issue 18 (8th November 2018) - Sharma, Satish; Abhyankar, Abhijit R.
Abstract: Distribution company (DISCOM) bids into day-ahead (DA) electricity market to serve the DA schedules of its loads put together along with distributed generation (DG) schedules. At real time (RT), the loads/DGs (participants) may deviate from their DA schedules and this deviation has to be settled at RT price. Any deviation by a participant on a feeder will change the total network losses. This leads to deviation penalty (cost) to DISCOM which should be allocated to the responsible participants. This deviation cost consists of two parts: first is due to deviation in DA power schedules and second is due to the change in network losses by these power deviations. In this article, the problem of allocating deviation cost is formulated as cooperative game and Shapley value is used to allocate this deviation cost. The deviation in schedules of DGs has also been modeled into game framework. The method has been tested on a system with different scenarios of power deviation of participants in RT. The results obtained are stable and consistent for both loads and DGs in deviation cost allocation.